2016
DOI: 10.1016/j.giq.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Media use during conflicts: Information seeking and political efficacy during the 2012 Mexican elections

Abstract: Public access to accurate and reliable information is fundamental to democracy and democratic decision-making. In emerging democracies, during political crises or controversial elections, reliable information is often difficult to obtain. In authoritarian regimes, citizens' perceptions of information reliability are tightly linked to trust in government, and both are typically low. Open government policies help build trust that is essential during protests or contentious elections. Uses and gratifications (U&G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
2
11
0
3
Order By: Relevance
“…As such, most of the news have been covered and are controlled by the editors. This finding is in line with many researches done previously (Kavanaugh, 2016;Siebert, Peterson, & Schramm, 1963;Al-Kandari & Hasanen, 2012;Salman et al, 2011). Some informants even said that it is wasted their time and money to buy newspapers which are bias.…”
Section: Public's Perceptions Of the Traditional News Media (Researchsupporting
confidence: 93%
See 3 more Smart Citations
“…As such, most of the news have been covered and are controlled by the editors. This finding is in line with many researches done previously (Kavanaugh, 2016;Siebert, Peterson, & Schramm, 1963;Al-Kandari & Hasanen, 2012;Salman et al, 2011). Some informants even said that it is wasted their time and money to buy newspapers which are bias.…”
Section: Public's Perceptions Of the Traditional News Media (Researchsupporting
confidence: 93%
“…Public access to accurate and reliable information is fundamental to democracy and democratic decision-making (Kavanaugh, 2016). Traditional media have historically served as a critical conduit of information to the public.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…shown that perceived information reliability predicts a greater sense of political information efficacy (PIE), that is, a person's belief that s/he is well informed and capable of forming opinions and acting on political information. Our finding that sharing information with family and friends leads to a greater sense of PIE is not only a contribution to research on PIE, but also consistent with our earlier analyses of citizen participation, information reliability and sharing and PIE during the 2012 elections in Mexico [27].…”
Section: Introductionsupporting
confidence: 90%